Heteropolyacid supported on acidic clay: a novel efficient catalyst for alkylation of ethylbenzene with dilute ethanol to diethylbenzene in presence of C-8 aromatics - Bokade, Vijay V.; Yadav, Ganapati D. (Journal of Molecular Catalysis A-Chemical, 2008)
Vapor phase alkylation of ethylbenzene with ethanol to diethylbenzene is industrially relevant. Diethylbenzene is an important raw material for the conversion of divinyl benzene monomer. Conventionally, it is prepared from diacetophenone by reduction. It is also prepared by vapor phase alkylation of ethylbenzene with ethylene using zeolitic catalysts. The efficacy of dodecatungsotphosphoric acid (DTPA) supported on acid treated clay has been evaluated in the current work in the alkylation of ethylbenzene with 80% (w/w) ethanol. 15% (w/w) DTPA/K-10 clay was found to be an efficient and robust catalyst. The use of aqueous ethanol and a mixed C-8 stream lowers the cost of production. A kinetic model is developed by studying the important process parameters with 15% (w/w) DTPA/K-10 as the catalyst. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Alkylation; diethylbenzene; Heteropolyacid; kinetics; Solid acids

Heteropolyacid supported on montmorillonite catalyst for dehydration of dilute bio-ethanol - Bokade, Vijay V.; Yadav, Ganapati D. (Applied Clay Science, 2011)
Vapour phase dehydration of dilute bio-ethanol (EtOH) to ethylene (E) and diethyl ether (DEE) is industrially relevant. Ethylene is an important raw material for many petrochemical products and Diethyl ether (DEE) can be used as an alternative fuel. The efficacy of montmorillonite (K-10) and dodecatungestophosphoric acid (DTPA) supported on montmorillonite (DTPA/K-10), has been evaluated in the current work in the dehydration of dilute bio-ethanol (80%m/m). The dehydration of ethanol and cracking of diethyl ether were studied independently. 30% m/m DTPA/K-10 was found to be more active with 74% ethanol conversion and 92% ethylene selectivity at 250 degrees C in comparison with other acid catalysts used. The merit of the process lies in its use of dilute bio-ethanol, a new avenue for ethylene production from a non-petroleum feedstock. Kinetic interpretation has been made by studying the important process parameters by using 30%m/m DTPA/montmorillonite as the catalyst. The mechanism of the dehydration of ethanol reaction suggests that two types of sites are responsible. The dehydration of ethanol and cracking of diethyl ether are second order reactions with weak adsorption of species. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Bio-ethanol; dehydration; Diethyl ether; Ethylene; Heteropolyacid

HPW anchored Meso-HZ-5, a novel catalyst for selective synthesis of ethyl levulinate biofuel by alcoholysis of biomass-derived furfuryl alcohol - Nandiwale, Kakasaheb Y.; Pande, Ashwini M.; Bokade, Vijay V. (Environmental Progress & Sustainable Energy, 2018)
Ethanolysis of biomass derived furfuryl alcohol (FA) produces ethyl levulinate (EL), a biofuel additive and precursor for -valerolactone synthesis. The present study is devoted to develop an efficient and an environmentally benign catalytic system for one-pot conversion of FA to EL biofuel, by revealing an insight of the catalytic mechanism. The catalytic activity of H-ZSM-5, Meso-HZ-5 (desilicated H-ZSM-5) and different percentage H3PW12O40(HPW) anchored to Meso-HZ-5 catalysts have been evaluated for the FA ethanolysis. As per our knowledge, this is the first research reporting the application of HPW anchored to Meso-HZ-5 catalysts for the conversion of FA into EL in biomass utilization. These catalysts were synthesized and characterized by Powder X-ray diffraction (XRD), N-2 physisorption and temperature programmed NH3 desorption (TPAD). Products of FA ethanolysis viz., 4,5,5-triethoxypentan-2-one (TEP), ethoxy-methyl- furan (EMF), diethyl ether (DEE), EL were identified by Gas Chromatography-Mass Spectroscopy (GC-MS) and quantified by flame ionization detector (GC-FID). The physicochemical properties of catalysts were found to correlate to the product distribution matrix. Moreover, influences of several process parameters such as catalyst amount, reactant molar ratio, temperature and time on the extent of FA ethanolysis were systematically investigated. Under optimized conditions, 15% (w/w) HPW/Meso-HZ-5 exhibited a remarkable catalytic performance with complete FA conversion (100%) along with 97% yield of EL, these activity values are superior than the previously reported studies. The present study provides an insight of the catalytic mechanism along with a potential environmental benign and the economic catalyst for the efficient synthesis of EL biofuel from the biomass-derived FA

HxZr3-xPW12O40 as an insoluble and reusable heteropolyacid for highly selective dehydration of fructose to 5-hydroxymethyl fufural in DMSO system - Mulik, Nagesh L.; Niphadkar, Prashant S.; Pandhare, Kiran V.; Bokade, Vijay V. (Chemistryselect, 2018)
Dehydration of fructose is a way to produce an important platform chemical such as 5-hydroxymethylfurfural (HMF) which is widely used to synthesize variety of renewable chemicals and fuel. Heteropoly acid, H3PW12O40 is highly soluble strong acidic catalyst with well-defined structure. This study reports the modification of soluble heteropoly acid to insoluble and reusable heteropolyacid (HxZr3-xPW12O40 ) by exchanging with Zr and investigation of its catalytic performance in selective transformation of renewable fructose to 5-HMF in Dimethyl sulfoxide (DMSO) system. The physico-chemical properties of H(x)Zr(3-x)PW(12)O(40)were derived from Powder-XRD, NH3-TPAD and FT-IR technique. The characterization of HxZr3-xPW12O40 revealed that the Keggin structure of HPA remained intact as proton replaced by Zr. The partial exchange of Zr in H2Zr1PW12O40 catalyst resulted in an increase in acidity, however further increase of Zr above 1, acidity was found to be decreased. At optimized reaction condition, 5-HMF yield of 85% with 100% selectivity was achieved with H1Zr2 PW12O40 catalyst at much lower reaction time of 10 min than reported. The catalyst was observed to be recoverable, reusable as compared to parent H3PW12O40.